The Role of Telemedicine in Expanding Healthcare Access: A Post-Pandemic Evaluation of Virtual Care Models - Montolalu, Ivan Adrian (Mandalika Institute, 2024)
The COVID-19 pandemic has accelerated the adoption of telemedicine, transforming it from a niche service into a cornerstone of modern healthcare delivery. This article evaluates the role of telemedicine in expanding healthcare access, focusing on virtual care models implemented during and after the pandemic. By analyzing a range of studies, reports, and data sources, this research highlights the benefits and limitations of telemedicine in improving healthcare accessibility, particularly in underserved and rural areas. Findings indicate that telemedicine has significantly enhanced patient engagement and access to specialist care, reduced healthcare costs, and improved management of chronic diseases. However, challenges such as digital divide issues, privacy concerns, and the need for robust regulatory frameworks remain. This study provides a comprehensive overview of current virtual care models, assesses their impact on healthcare equity, and offers recommendations for optimizing telemedicine practices to ensure sustainable and equitable healthcare access in the post-pandemic era.